2012
DOI: 10.2169/internalmedicine.51.6884
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hu-associated Paraneoplastic Encephalomyelitis with Esophageal Small Cell Carcinoma

Abstract: A 63-year-old woman had anti-Hu-associated paraneoplastic encephalomyelitis (anti-Hu syndrome) caused by esophageal small cell carcinoma (SCC). The patient developed bilateral limbic encephalitis, followed by myelitis, brain stem encephalitis, and autonomic failure. Extensive examination demonstrated SCC of the abdominal lymph nodes that was retrospectively diagnosed as metastasis of esophageal SCC on autopsy. The neuropathological findings were characterized by widespread neuronal loss and gliosis in the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In this case, lung adenocarcinoma was suspected clinically because an adenocarcinoma component was identified on bronchial brush cytology. 8 In several studies, neuron loss, gliosis, microglial cell activation and the presence of infiltrating leukocytes have been reported as neuropathologic changes in this condition [9][10][11][12][13][14][15][16][17][18] However, neurons were preserved and levels of infiltrating leukocytes were relatively mild in our patient. 6 This poorly differentiated NSCLC is characterized by having at least 10% spindle and/or giant cells or a spindle and giant cell alone.…”
Section: Discussionmentioning
confidence: 46%
“…In this case, lung adenocarcinoma was suspected clinically because an adenocarcinoma component was identified on bronchial brush cytology. 8 In several studies, neuron loss, gliosis, microglial cell activation and the presence of infiltrating leukocytes have been reported as neuropathologic changes in this condition [9][10][11][12][13][14][15][16][17][18] However, neurons were preserved and levels of infiltrating leukocytes were relatively mild in our patient. 6 This poorly differentiated NSCLC is characterized by having at least 10% spindle and/or giant cells or a spindle and giant cell alone.…”
Section: Discussionmentioning
confidence: 46%
“…These paraneoplastic-associated antibodies often cause LE. It has been shown that LE usually refers to a tumor anti-neuron antibody (such as anti-Hu) and cell surface antibody [alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic antibody (AMPAR)] ( 43 ). The clinical features of LE are short-term memory loss, seizures, irritability, depression, and cognitive decline in subacute onset.…”
Section: Discussionmentioning
confidence: 99%